Advanced engineering mathematics - Zill, Dennis G., 1940- 4 0 16; 5 (Burlington, MA : Jones & Bartlett Learning, 2022)
Modern and comprehensive, the new seventh edition of award-winning author, Dennis G. Zill's Advanced Engineering Mathematics is a compendium of topics that are most often covered in courses in engineering mathematics, and is extremely flexible to meet the unique needs of courses ranging from ordinary differential equations, to vector calculus, to partial differential equations. A key strength of this best-selling text is the author's emphasis on differential equations as mathematical models, discussing the constructs and pitfalls of each. An accessible writing style and robust pedagogical aids guide students through difficult concepts with thoughtful explanations, clear examples, interesting applications, and contributed project problems--
Includes index
Keywords: 2 -- 0; 6; Engineering mathematics -- 20; 20; 2